Analysis of Determinants Affecting the Distribution of MSME Funds in Indonesia: A Study of the VECM Approach - Ashary, M. Habib; Irsyadillah, Muhammad Ridha; Laila, Nisful (Faculty of Economics and Management, 2025)
This study analyzes the dynamic relationship between Islamic monetary instruments (SBIS, PUAS, and the PLS mechanism) and the distribution of MSME financing in Indonesia, using a Vector Error Correction Model (VECM) for the period January 2014 to December 2023. The estimation results indicate significant policy transmission challenges: SBIS has a negative and significant effect on MSME financing. This crucial finding indicates that SBIS functions as a “liquidity trap,” encouraging Islamic banks to place funds in low-risk liquid instruments rather than in risky real-sector financing, such as MSMEs. Meanwhile, PUAS and the underlying PLS mechanism are statistically insignificant, indicating risk aversion and operational barriers to profit-sharing contracts. IRF and FEVD analyses reinforce the conclusion that policy transmission remains weak, with MSME financing variations dominated by internal bank shocks. Theoretically, this study reveals a critical gap in the Mudarabah-based monetary framework, where liquidity instruments sacrifice the goal of promoting the real economy. The practical implications require regulators to redesign liquidity instruments (such as SBIS) to better encourage real-sector incentives, thereby strengthening the alignment between sharia principles and national economic development.